2020
DOI: 10.3390/cancers12010185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complexity of Diffuse Large B-Cell Lymphoma: Can It Be a Roadmap for Precision Medicine?

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma; it features extreme molecular heterogeneity regardless of the classical cell-of-origin (COO) classification. Despite this, the standard therapeutic approach is still immunochemotherapy (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone—R-CHOP), which allows a 60% overall survival (OS) rate, but up to 40% of patients experience relapse or refractory (R/R) disease. With the purpose of searching for new clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 120 publications
0
22
0
1
Order By: Relevance
“…Since the introduction of rituximab in combination with conventional chemotherapy, significant improvement of treatment outcomes has been observed [ 4 , 5 ]. Nevertheless, treatment strategies are often highly individualized in elderly patients, who are more likely to suffer from life-threatening chemotherapy-related toxicity due to chronic or weakness-associated diseases [ 6 ]. As a result, nationwide database analyses in many countries showed that more than 50% of the elderly patients did not receive anthracycline-containing regimens as the first-line treatment [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of rituximab in combination with conventional chemotherapy, significant improvement of treatment outcomes has been observed [ 4 , 5 ]. Nevertheless, treatment strategies are often highly individualized in elderly patients, who are more likely to suffer from life-threatening chemotherapy-related toxicity due to chronic or weakness-associated diseases [ 6 ]. As a result, nationwide database analyses in many countries showed that more than 50% of the elderly patients did not receive anthracycline-containing regimens as the first-line treatment [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…SHUFANG XIE 1,2* , WEIMIN FAN 2,3* , CHEN YANG 2,4 , WEN LEI 5 , HONGYING PAN 6 , XIANGMIN TONG 2,7 , YI WU 8 and SHIBING WANG 2,7 patients suffer from treatment-refractory or relapsed disease with associated high mortality rate (3,4).Chemotherapeutic drugs can cause extensive DNA damage within both tumor and healthy cells (5), such that even patients that survive chemotherapy suffer significant systemic toxicity and renal failure in a dose-dependent manner (6).…”
Section: Beclin1-armed Oncolytic Vaccinia Virus Enhances the Therapeutic Efficacy Of R-chop Against Lymphoma In Vitro And In Vivomentioning
confidence: 99%
“…Diffuse large B cell lymphoma (DLBCL) is the most common form of NHL, accounting for 30–40% of new cases. Rituximab, Cyclophosphamide, Epirubicin, Vindesine, Prednisolone (R-CHOP) is the first-line standard of care treatment for these patients and can achieve a 60% overall survival (OS) rate ( 2 ); however, up to 40% of patients suffer from treatment-refractory or relapsed disease with associated high mortality rate ( 3 , 4 ). Chemotherapeutic drugs can cause extensive DNA damage within both tumor and healthy cells ( 5 ), such that even patients that survive chemotherapy suffer significant systemic toxicity and renal failure in a dose-dependent manner ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a proteasome inhibitor used to suppress Diffuse large B-cell lymphoma (DLBCL) progression [ 223 , 224 , 225 ]. DLBCL is the most frequent non-Hodgkin lymphoma, showing variable clinical presentations as well as variable therapy responses [ 226 , 227 , 228 ]. In vitro studies on DLBCL CRL-2630 cells showed that BTZ treatment significantly inhibited the proliferation of DLBCL CRL-2630 cells [ 229 ].…”
Section: Hmga Proteins As Targetable Markersmentioning
confidence: 99%